2017
DOI: 10.1103/physrevlett.119.021102
|View full text |Cite
|
Sign up to set email alerts
|

γ -ray Constraints on Decaying Dark Matter and Implications for IceCube

Abstract: Utilizing the Fermi measurement of the gamma-ray spectrum toward the Inner Galaxy, we derive some of the strongest constraints to date on the dark matter (DM) lifetime in the mass range from hundreds of MeV to above an EeV. Our profile-likelihood based analysis relies on 413 weeks of Fermi Pass 8 data from 200 MeV to 2 TeV, along with up-to-date models for diffuse gamma-ray emission within the Milky Way. We model Galactic and extragalactic DM decay and include contributions to the DM-induced gamma-ray flux res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
201
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(217 citation statements)
references
References 144 publications
(202 reference statements)
12
201
4
Order By: Relevance
“…Nevertheless, in these models the DM decays will generically also produce photons which can be searched for in other experiments. In particular [7] considered the limits obtained with the Fermi -LAT, and demonstrated that models which seek to explain the majority of the IceCube flux appear to be in tension with the gamma-ray data. HAWC, with its ability to study gamma-rays at even higher energy than the Fermi -LAT, can also constrain this parameter space, as we demonstrate in this work.…”
Section: Jcap02(2018)049mentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, in these models the DM decays will generically also produce photons which can be searched for in other experiments. In particular [7] considered the limits obtained with the Fermi -LAT, and demonstrated that models which seek to explain the majority of the IceCube flux appear to be in tension with the gamma-ray data. HAWC, with its ability to study gamma-rays at even higher energy than the Fermi -LAT, can also constrain this parameter space, as we demonstrate in this work.…”
Section: Jcap02(2018)049mentioning
confidence: 99%
“…[20] and in particular [21] for a recent summary, the presence of a large contribution from DM cannot at present be excluded using the IceCube data alone. Accordingly, a number of models have been developed which explain the high-energy neutrino flux with DM [7,. Generally these models seek to explain the highest energy neutrinos observed by IceCube -the so-called High Energy Starting Events (HESE)-however some also deal with a putative excess in the lower energy Medium Energy Starting Events (MESE) [45], which has been discussed in the context of DM [46] and astrophysics [47][48][49].…”
Section: Jcap02(2018)049mentioning
confidence: 99%
See 2 more Smart Citations
“…For energies of the order of the electroweak scale, we applied the limit from the Fermi satellite observation of the galactic halo [42], and the extragalactic flux [43] (see also Ref. [44] for a recent combined analysis 10 ). We present our results in Fig.…”
Section: B Icecube Constraintsmentioning
confidence: 99%